Evaluation of Tools and Slicing Techniques for Efficient Verification of UML/OCL Class Diagrams. (27th September 2011) - Shaikh, Asadullah; Wiil, Uffe Kock; Memon, Nasrullah
Abstract : UML/OCL class diagrams provide high-level descriptions of software systems. Currently, UML/OCL class diagrams are highly used for code generation through several transformations in order to save time and effort of software developers. Therefore, verification of these class diagrams is essential in order to generate accurate transformations. Verification of UML/OCL class diagrams is a quite challenging task when the input is large (i.e., a complex UML/OCL class diagram). In this paper, we present (1) a benchmark for UML/OCL verification and validation tools, (2) an evaluation and analysis of tools available for verification and validation of UML/OCL class diagrams including the range of UML support for each tool, (3) the problems with efficiency of the verification process for UML/OCL class diagrams, and (4) solution for efficient verification of complex class diagrams.